2017
DOI: 10.1038/srep40449
|View full text |Cite
|
Sign up to set email alerts
|

LPS promotes Th2 dependent sensitisation leading to anaphylaxis in a Pru p 3 mouse model

Abstract: Pru p 3 is the major peach allergen in the Mediterranean area. It frequently elicits severe reactions, limiting its study in humans, raising the need for animal models to investigate the immunological mechanisms involved. However, no anaphylaxis model exists for Pru p 3. We aimed to develop a model of peach anaphylaxis by sensitising mice with Pru p 3 in combination with lipopolysaccharide (LPS) as an adjuvant. Four groups of mice were sensitised intranasally: untreated; treated with Pru p 3; treated with LPS;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
48
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(52 citation statements)
references
References 53 publications
(74 reference statements)
3
48
0
1
Order By: Relevance
“…We confirmed the mice were anaphylactic after the 5 week sensitization period by performing an intraperitoneal challenge with Pru p 3, observing similar in vivo and in vitro data to those previously reported (data not shown). The in vivo evaluation showed that Sensitized, Treated with D 1 (Prup3)+CpG mice maintained a body temperature comparable to basal conditions and to that of the Non‐Sensitized group.…”
Section: Resultssupporting
confidence: 91%
“…We confirmed the mice were anaphylactic after the 5 week sensitization period by performing an intraperitoneal challenge with Pru p 3, observing similar in vivo and in vitro data to those previously reported (data not shown). The in vivo evaluation showed that Sensitized, Treated with D 1 (Prup3)+CpG mice maintained a body temperature comparable to basal conditions and to that of the Non‐Sensitized group.…”
Section: Resultssupporting
confidence: 91%
“…The lack of increase in Pru p 3‐specific IgE levels suggests the increased IgE is attached to cells, although further experiments will be needed to investigate this, as there is a clear tendency for increased levels in the anaphylactic animals. These findings are in line with previous studies using this model, however, other allergy models have found IgE secreting cell numbers to be less than IgG1 secreting cells, for example, in a murine model of allergic asthma . Pru p 3‐sIgG1 levels were also higher for anaphylactic animals versus Pru p‐3 only receiving animals; interestingly this is also in contrast with the antibody‐secreting cell numbers, which were higher for sIgE.…”
Section: Resultssupporting
confidence: 91%
“…Female Balb/c mice aged 4–5 weeks (Janvier Lab, Saint‐Berthevin Cedex, France) were sensitized to peach using intranasally administered Pru p 3 in combination with LPS and challenged intraperitoneally as described previously . These will be referred to as anaphylactic mice.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study used peach allergen Pru p 3 with lipopolysaccharide as adjuvant for intranasal sensitization, and anaphylaxis could be elicited by intraperitoneal challenge [60]. The authors suggested this model to be suitable for testing immunotherapeutic strategies.…”
Section: Introductionmentioning
confidence: 99%